Transisi Akuntansi Menuju Digitalisasi - Anjeli Saputri; Nurul Fauziyyah (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2023)
The issue of the end of accounting in the digital era will threaten the existence of the accounting profession itself. The purpose of this study is to provide an overview of the accounting transition process towards digitization both in terms of profession, work assignments, learning process, and other related matters. As well as the strategy of the accounting profession in the digital era. The research method uses descriptive qualitative methods with interview data collection techniques involving accountant educators and accounting students from various public and private universities in Indonesia. The results of this study indicate that digitalization requires the accounting profession to adapt itself to the digital era. The role of the accounting profession, which is no longer focused on journalizing as it used to be, requires them to prepare themselves more maturely to face their main competitors, namely technology and programmers. Currently, at the tertiary level, learning information systems in the accounting major is urgently needed by simultaneously increasing the number of case studies to train creative thinking in decision making to prepare prospective accounting professions in the digital era.